Time-resolved imaging of positive pulsed corona-induced surface streamers on TiO2 and γ-Al2O3-supported Ag catalysts. (13th September 2016) - Kim, Hyun-Ha; Teramoto, Yoshiyuki; Ogata, Atsushi
Abstract: We report the first instance of time-resolved imaging of surface streamers in air propagating on the surface of titanium dioxide (TiO2 ) and alumina ( γ -Al2 O3 ) beads at ambient temperature and atmospheric pressure. The propagation velocity of primary streamers was found to be dependent primarily on the applied voltage and the type of catalyst. The presence of Ag nanoparticles enhanced the propagation velocity of primary streamers in both TiO2 and γ -Al2 O3 . Some of the primary streamers passed through a partial discharge, which resulted in enhanced discharge intensity. Through successive steps, the partial discharge served as a staging point for primary streamers, and promoted their propagation toward the next catalyst bead. For a given configuration and catalyst, the velocity of the primary streamer was largely influenced by applied voltage and catalyst type. For a mesh-to-mesh reactor with Ag/ TiO2 catalyst, the primary streamer reached about 660 km s −1 . Secondary streamers occurred with much slower velocities after the primary streamer had disappeared. In contrast to primary streamers, secondary streamer velocities were almost completely independent of the applied voltage on both TiO2 (150  ±  50 km s −1 ) and γ -Al2 O3 (70  ±  10 km s −1 ). Detailed time-resolved imaging data on surface streamers can provide important insight into understanding and modeling plasma-catalysis, which can accelerate the progress of research and development in this area.